2022
DOI: 10.3390/jof8010074
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Use of Isavuconazole as Primary Therapy for Invasive Fungal Infections in High-Risk Patients with Hematologic Malignancy or Stem Cell Transplant

Abstract: (1) Introduction: Invasive fungal infections (IFIs) are a major cause of morbidity and mortality among immunocompromised patients with hematologic malignancies (HM) and stem cell transplants (SCT). Isavuconazole was approved by FDA as a primary therapy for Invasive Aspergillosis (IA) and Mucormycosis. The aim of this study is to look at the real-world use of Isavuconazole in patients with HM and evaluate their clinical outcomes and safety. (2) Methods: We conducted a retrospective study of HM patients at MD An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
7
1
1
Order By: Relevance
“…In our study, the favorable response to isavuconazole at 6 and 12 weeks, and at the end of treatment, was 90%. This is higher than the 45% response rate reported in the SECURE trial, and the 47% and 42% reported at 6 and 12 weeks, respectively, in previous studies [ 13 , 30 ].…”
Section: Discussioncontrasting
confidence: 73%
“…In our study, the favorable response to isavuconazole at 6 and 12 weeks, and at the end of treatment, was 90%. This is higher than the 45% response rate reported in the SECURE trial, and the 47% and 42% reported at 6 and 12 weeks, respectively, in previous studies [ 13 , 30 ].…”
Section: Discussioncontrasting
confidence: 73%
“…The frequent use of a second antifungal agent mirrors similar real-life studies in hematological patients. 34 The eventual synergistic effect of combining isavuconazole with L-AmB or an echinocandin remains to be established, with some supporting in vitro and animal data 35,36 and clinical reports. 37 The two factors that are found to independently predict the lack of clinical response-disseminated IMD and elevated serum AST levels-are markers of higher fungal burden and preexisting liver toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analyses of studies, which include patients with hematological malignancies, show amphotericin B to be the agent of choice associated with a favorable outcome [ 21 ]. The newer triazoles, posaconazole and isavuconazole, can be alternatives to amphotericin B when stepdown therapy is needed or the patients cannot be treated with amphotericin B [ 22 , 23 ]. A drawback of these relatively new agents is the limited number of studies in the pediatric population [ 2 ].…”
Section: Discussionmentioning
confidence: 99%